2020
DOI: 10.2147/dmso.s284120
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association of Circulating Selenium Concentrations with Diabetes Mellitus</p>

Abstract: Purpose: The relationship between circulating selenium and diabetes mellitus (DM) remains inconsistent. Therefore, the relationship between circulating selenium and DM was investigated in the present study. Patients and Methods: All participants (aged ≥18 years) were included from the National Health and Nutrition Examination Survey (NHANES) 1999-2006. Selenium concentrations from the fasting serum samples were determined using inductively coupled mass spectrometry, then grouped into quartiles. Odds ratios (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…Liao et al analysed data of 2903 participants from the US National Health and Nutrition Examination Survey (NHANES), highlighting that T2D patients have higher selenium levels compared with healthy subjects. Notably, the risk association was particularly higher in younger women [ 315 ]. Similarly, in a large population of Italian adults from a Moli-sani study cohort (21,335 subjects), a high dietary selenium intake was recently associated with increased risk of hospitalization for diabetes [ 316 ].…”
Section: Type-2 Diabetesmentioning
confidence: 99%
“…Liao et al analysed data of 2903 participants from the US National Health and Nutrition Examination Survey (NHANES), highlighting that T2D patients have higher selenium levels compared with healthy subjects. Notably, the risk association was particularly higher in younger women [ 315 ]. Similarly, in a large population of Italian adults from a Moli-sani study cohort (21,335 subjects), a high dietary selenium intake was recently associated with increased risk of hospitalization for diabetes [ 316 ].…”
Section: Type-2 Diabetesmentioning
confidence: 99%
“…While some studies report significant Se concentration between women and men [ 19 ], other studies report a sex-specific association of Se with cancer risk, cognitive performance, serum lipid levels and first total and ischemic stroke risk [ 56 , 57 , 58 , 59 ]. Regarding the specific association of Se with T2D and insulin resistance, a piece of recent evidence shows that Se is independently associated with T2D in adult women with a mean level of Se of 136.4 ± 19.6 μg/L in the United States [ 60 ]. Later evidence in the French population also shows a sex-specific association between higher plasma Se concentration and lower risk of developing dysglycemia after nine years following in men with baseline plasma Se mean levels of 1.08 ± 0.21 μmol/L [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased superoxide production is the central and major mediator of diabetic tissue damage. Based on the role of Se in glucose metabolism and antioxidant defense, Se may be involved in the pathogenesis of T2DM [ 126 ].…”
Section: Type 2 Diabetes (T2dm)mentioning
confidence: 99%
“…Several studies have demonstrated the importance of Se in T2DM patients. A case-control study showed that T2DM patients had higher levels of Se than healthy individuals [ 126 ]. A case cohort study also found that higher serum Se levels were associated with an increased risk of T2DM [ 127 ].…”
Section: Type 2 Diabetes (T2dm)mentioning
confidence: 99%